Comparative Analysis of the Clinical Efficacy of Intrastromal Keratoplasty using a Digital Marking Device in Patients with Keratoconus - A. V. Tereshchenko; I. G. Trifanenkova; E. N. Vishnyakova; S. K. Dem’yanchenko; E. А. Nikolaev (Oftalʹmologiâ, 2020)
Purpose — to perform a comparative analysis of the clinical efficacy of intrastromal keratoplasty (ISKP) in patients with keratoconus during surgery with and without Verion digital marking device.Patients and methods. 37 patients (50 eyes) with corneal astigmatism up to -5.0 diopters were included in the study. These patients were operated with the femtolaser method of ISKP with implantation of corneal segments. The average age of the patients was 27.96 ± 3.40 years. The observation period is from 3 to 12 months. All patients were divided into two groups depending on the surgical technique: Verion-assisted, using a digital marking device and taking into account the angle of cyclotorsia, or standard, without taking into account the angle of cyclotorsia. The first main group included 28 eyes (56 %), the second control group included 22 eyes (44 %) accordingly.Results. The functional results after ISKP in both groups were quite good. Stabilization of functional parameters and keratometric data was noted in the postoperative period, by 3 months. Patients of the main group showed a statistically significant (p < 0.05) increase in average uncorrected visual acuity to 0.50 ± 0.16, and visual acuity with maximum correction to 0.70 ± 0.12 (p < 0.05). The average keratometry of the weak meridian decreased to 44.3 ± 1.4 diopters, the average keratometry of the strong meridian decreased to 50.8 ± 3.2 diopters. Patients in the control group showed a statistically significant (p < 0.05) increase in average uncorrected visual acuity to 0.45 ± 0.12, and visual acuity with maximum correction to 0.60 ± 0.17. The average values of keratometry of the weak meridian decreased to 45.3 ± 1.8 diopters, the average values of keratometry of the strong meridian decreased to 51.8 ± 2.2 diopters. The results of the vector analysis reliably indicate a significantly higher accuracy of the Verion-assisted ISKP. Which is confirmed by the achieved indicators of the “success” index, the calculated astigmatism vector close to the actual postoperative astigmatism vector, the smaller the magnitude of the astigmatism axis difference vector compared to the control.Conclusion. The use of the Verion-assisted intrastromal technique for keratoconus reduces the risk of erroneous positioning of the corneal segments in the tunnel during transferring diagnostic data to the operating room. Taking into account the angle of cyclotorsia during cutting into the intrastromal tunnel increases the effective correction of the cylindrical component of refraction, which is confirmed by the main coefficients of the vector analysis by N. Alpins.